Multiple switchable circularly polarized luminescence from nucleotide/terbium(iii) complexes. (7th February 2023) - Yang, Chujing; Zhang, Zhiwei; Chen, Jingqi; Zhang, Xinying; Dai, Yankai; Li, Xuyi; Chen, Yingying; Xu, Jiaqiang; Feng, Lingyan
Abstract : Nucleotide and terbium complexes exhibit circularly polarized luminescence and can be reversed by a magnetic field, pH, and nucleotides. Abstract : We found that the complexes of nucleotides and terbium(iii ) exhibit circularly polarized luminescence (CPL). The CPL of GMP/Tb/Ag coordination polymer nanoparticles (CPNs) was converted by a magnetic field and pH. The CPL of the purine nucleobase of nucleotides was opposite to that of the pyrimidine nucleobase. GMP/Tb/Ag CPNs could be used as advanced safety coatings and acid–base switches, and Tb/Ag could be used as CPL probes for rapid differentiation of nucleotides, which provided ideas for multiple transformations and applications of CPL.